The Adoption of New Technologies and the Age Structure of the Workforce - Jenny Meyer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper provides firm-level evidence for the relationship between the age structure of the workforce and the adoption of new or significantly improved technologies in service sector firms. Furthermore, it closes a research gap by analyzing the joint impact of the age of the workforce and the enhancement of teamwork on the probability of adopting new technologies. The empirical analyses, that are based on a data set of 356 German firms from the knowledge-intensive services and ICT services sector, reveal three findings: Firstly, firms with a higher share of younger employees are more likely to adopt new technologies and the older the workforce is, the less likely is the adoption of new technologies. Secondly, the distribution of the age of the workforce has no significant impact on the probability of adopting new technologies. And thirdly, firms which enhanced their teamwork and have a higher share of younger workers are less likely to adopt new technologies whereas firms that enhanced their teamwork and have a higher share of older employees are more likely to adopt new technologies.
Keywords: O31; J14; 330; age structure of the workforce; adoption of new technologies; ICT intensive services; Technologiewahl; Innovationsdiffusion; Arbeitskräfte; Lebensalter; Gruppenarbeit; Unternehmensdienstleistung; EDV-Dienstleistung; Deutschland